Nathan Cummings Foundation - Campion, Ellie; Edwards, Dwayne; Wayman, Bradley; Williams, Anna, active 2019; Goetzmann, William N.; Rosenthal, Jean W., 1945- (London : Yale School of Management, 2019)
In 2017, The Nathan Cummings Foundation (NCF) decided to go "all in" for a mission-related investment approach. The Board set a goal of putting all $443 million of its endowment towards investments in line with the mission of the foundation. The Nathan Cummings Foundation Investment Committee and Board of Trustees had studied the decision for over a year, guided by Sonen Capital consultants. The Board voted 100% to support this new direction and new goals for financial investments, but many questions remained. How could NCF operationalize and integrate this new strategy? What changes would it need to make to support the investment strategies' long-term success? How could NCF measure and track its progress and success with this new strategy?
Originally Published InCampion, E., Edwards, D., Wayman, B., Williams, A., Goetzmann, W., & Rosenthal, J. (2019). Nathan Cummings Foundation. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nathan Cummings Foundation -- Case studies; Endowments -- United States -- Case studies; Investments -- Moral and ethical aspects -- United States -- Case studies